The auditor's reputation, the previous year's audit opinion, and the going concern audit opinion: The moderating role of financial distress - Ulhaq Taufiqurrahman, Dhiya; Suripto, Suripto (Universitas Pamulang, 2024)
This study examines the effect of a public accounting firm's reputation and the previous year's audit opinion on going concern audit opinion. We use Indonesian property and real estate sector companies as the research sample. We also analyze the moderating role of financial distress in the relationship between public accounting firm reputation and the audit opinion of the previous year's ongoing concern. The results of this study found that the previous year's audit opinion hurt going concern audit opinion. Public accounting firm reputation has not been proven to affect going concern audit opinion, while financial distress has not been proven to moderate the effect of public accounting firm reputation or previous year audit opinion on going concern audit opinion.